Polyneuropathy: A Rare and Challenging Presentation of Essential Mixed Cryoglobulinemia - Ahmed Taha MD; Mohamed Taha MD; Roaa Ahmed MBBS; Gianna Meckler; Narothama Aeddula MD; Jason Meckler MD (SAGE Publishing, 2021)
A 49-year-old male presented with acute chronic sensory motor bilateral lower extremity polyneuropathy. Electromyography showed bilateral acute sensory motor axonal polyneuropathy. Lumbar spine magnetic resonance imaging showed diffuse bone marrow replacement and bilateral ankylosing spondylitis. Laboratory workup revealed elevated inflammatory markers and low G6PD (glucose-6-phosphate dehydrogenase) level. Due to elevated acute phase reactants, inflammatory polyneuropathy was suspected; patient was treated accordingly with resolution of neuropathy. Three months later, he relapsed and presented with disabling polyneuropathy and renal impairment, which prompted renal biopsy. Renal histopathology revealed the, otherwise mysterious, etiology, essential mixed cryoglobulinemia. Essential mixed cryoglobulinemia was not considered initially due to the absence of classic systemic manifestations of autoimmune disorders.